SURG-25. A NOVEL BIO-IMPEDANCE SPECTROSCOPY SYSTEM REAL-TIME INTRAOPERATIVELY DISCRIMINATES GLIOBLASTOMA FROM BRAIN TISSUE IN MICE - Zhang, Yuhui; Xu, Shoupei; Min, Weijie; Shen, Linyong; Zhang, Yanan; Yue, Zhijian (Neuro-oncology (Charlottesville, Va.), 2017)
“Tumor boundary” is difficult to be identified during glioblastoma (GBM) resection. Based on the bio-impedance difference between GBM and brain tissue, a novel bio-impedance spectroscopy system was developed to distinguish tumor from brain tissue, and detect the “tumor boundary” for the improvement of the effectiveness and safety during operation. To study this, the intracranial GBM model in mice was established. A tetrapolar bio-impedance spectroscopy-based measuring box system was invented to measure tissue impedance. Tumor and brain tissue were collected from mice, and respectively loaded into the box system for impedance measurement. The bio-impedance measurements were performed under small alternating current signal in the frequency from 1Hz to 1MHz and then analyzed particularly from 20Hz to 250K Hz. The spectroscopic analysis results revealed distinctive impedance difference between GBM and brain tissue in low and middle frequency zone (P<0.01). Furthermore, another novel impedance spectroscopy-based measurement system was design and invented to measure tissue impedance in vivo. The tumor and brain tissue were intactly measured with the detector put on the surface of the tissue. The spectroscopic analysis results showed distinctive impedance difference between GBM and brain tissue in the frequency from 100K Hz to 250K Hz (P<0.01). The slope index of the impedance curve from 100K Hz to 250K Hz was calculated. It was increased by 352.57% with U87 tumor compared to brain tissue, and 150.23% with C6 tumor compared to brain tissue (P<0.05). Although further research is needed for the future application in clinic, the novel bio-impedance spectroscopy-based measurement system provides an alternative method to discriminate GBM from brain tissue for the detection of the “tumor boundary”.